Gender, tourism, and participatory appraisals at the Corumbau Marine Extractive Reserve, Brazil - Di Ciommo, Regina C. [UNESP] (My University, 2007)
The Corumbau Marine Extractive Reserve was created in a region of rich biodiversity, located in the South of Bahia State, Brazil, to meet the revindications of artisanal fishermen in a context of increasing predatory industrial fisheries. The aim of the Marine Extractive Reserve is to improve the sustainability of fisheries stocks and the economy of artisanal fishermen's families, protecting the local biodiversity for the locals' collective use. However, at Corumbau the natives are facing social problems that have increased due to tourism growth. The present research contributes to the Management Plan in sectors that are crucial to assess the aspirations and subjective aspects related to the natives' daily life at individual, familiar and communitary levels. The Participatory Appraisal with a Gender Equity Perspective (PAGP) was applied to five communities at RESEX Corumbau, showing, by gender, the greatest problems artisanal fisheries' families are facing. Tourism is growing in the area, reflecting the residents different and contradictory interests. It can develop commerce and jobs, but also intensify some social and environmental problems in this area. © Society for Human Ecology.
Keywords: Artisanal fisheries; Gender; Marine extractive reserves; Participatory appraisal; Protected areas; Tourism